2014
DOI: 10.1002/chem.201405240
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Quinoxalines by Using TMP Bases: Preparation of Tetracyclic Heterocycles with High Photoluminescene Quantum Yields

Abstract: Tetracyclic heterocyclest hat exhibit high photoluminescence quantum yields were synthesized by anellation reactions of mono-, di-, and trifunctionalized 2,3-dichloroquinoxalines. Thus, treatment of 2,3-dichloroquinoxaline with TMPLi (TMP = 2,2,6,6-tetramethylpiperidyl) allows ar egioselective lithiationi np osition 5. Quenching with variouse lectrophiles (iodine, (BrCl 2 C) 2 ,a llylic bromide, acid chloride, aryl iodide)l eads to 5-functionalized 2,3-dichloroquinoxalines. Furtherf unctionalization in positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Wall precursor 24 was prepared by Suzuki cross‐coupling with the functionalized HBD groups and quinoxaline intermediate 25 , which was accessed through selective iodination of 2,3‐dichloroquinoxaline (Scheme A). This strategy provided a versatile synthetic approach for accessing a variety of quinoxaline walls by installing HBD groups in the final synthetic step (for more details, see Section S1 in the Supporting Information), which significantly improved the method previously undertaken in functionalizing quinoxaline walls that relied on benzothiadiazole intermediates, such as 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Wall precursor 24 was prepared by Suzuki cross‐coupling with the functionalized HBD groups and quinoxaline intermediate 25 , which was accessed through selective iodination of 2,3‐dichloroquinoxaline (Scheme A). This strategy provided a versatile synthetic approach for accessing a variety of quinoxaline walls by installing HBD groups in the final synthetic step (for more details, see Section S1 in the Supporting Information), which significantly improved the method previously undertaken in functionalizing quinoxaline walls that relied on benzothiadiazole intermediates, such as 26 .…”
Section: Resultsmentioning
confidence: 99%
“…UV/Vis spectra of reactants 1 e , 2 b and their products 3 m , 3′m were recorded, and the tetracyclic heteroacenes ( 3 m and 3′m ) showed strong absorption peak at 398 nm. Importantly, the conjugates 3 a , 3 c , 3 d , 3 m , and 3′m with different substituents exhibited strong photoluminescence (PL; Supporting Information, Figure S12) in the visible light spectral region …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above,i ti sh ighly desirable to develop ag eneral and highly efficient method for bioorthogonal ligation and cleavage.W er ealized that reaction of odichloroquinoxalines with o-dithiophenols could be performed in organic solvents under the irradiation of light [22] or base-promoted conditions. [23] We surmised that the selective reactions of o-dichloroquinoxalines and their derivatives with o-dithiophenols could be used in bioorthogonal ligations and cleavages.F irstly,v arious chloroquinoxalines and odithiophenols were prepared (Supporting Information, Schemes S1 and S2), and then couplings of chloroquinoxalines with o-dithiophenols were attempted in water/N,Ndimethylformamide (DMF) or phosphate buffer saline (PBS, pH 7.4)/DMF (Table 1). Wide investigations on the reagents and reaction conditions were performed, and some reactions of o-dichloroquinoxalines or mono-substituted chloroquinoxalines with o-dithiophenols readily occurred in high yields with excellent selectivity (Supporting Information, Tables S1-S7).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the conjugates 3a, 3c, 3d, 3m,a nd 3' 'm with different substituents exhibited strong photoluminescence (PL;S upporting Information, Figure S12) in the visible light spectral region. [23] Proteins are ak ind of important biopolymers,a nd their chemical modification can provide av ariety of purposes in chemical biology and medicine, [24] such as installing afluorophore [8,25] or binding partner [26] on proteins.B efore investigating bioorthogonal reaction for protein modification, we first attempted to use GSH as amodel peptide to appraise the CQ-DT reactions.The experiments showed that the reactions worked well in 60 min and almost quantitative conjugates were observed by HPLC and ESI-MS (Supporting Information, Figures S13-S40). With these encouraging small molecules results in hand, we examined the CQ-DT reactions outlined above with am odel protein to evaluate their potential as an ovel bioorthogonal method.…”
Section: Entrymentioning
confidence: 99%